2010
DOI: 10.1293/tox.23.63
|View full text |Cite
|
Sign up to set email alerts
|

No Mutations of Lysophosphatidic Acid Receptor Genes in Lung Adenocarcinomas Induced by N-Nitrosobis(2-hydroxypropyl)amine in Rats

Abstract: Lysophosphatidic acid (LPA) is a bioactive phospholipid that stimulates cell proliferation and migration, and protects cells from apoptosis. It interacts with specific G protein-coupled transmembrane receptors. Recently, frequent mutations of the LPA receptor-1 (LPA1) gene were detected in rat lung adenocarcinomas induced by N-nitrosobis(2-hydroxypropyl)amine (BHP). In this study, to evaluate the involvement of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2010
2010
2012
2012

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 22 publications
(25 reference statements)
0
4
1
Order By: Relevance
“…These results suggest that mutations of the Lpar1 gene may be involved in the acquisition of growth advantage from adenomas to adenocarcinomas during rat lung carcinogenesis induced by BHP 20 . By contrast, no mutation of the Lpar2 , Lpar3 , Lpar4 and Lpar5 genes was detected in this model 21 .…”
Section: Genetic Alterationscontrasting
confidence: 61%
“…These results suggest that mutations of the Lpar1 gene may be involved in the acquisition of growth advantage from adenomas to adenocarcinomas during rat lung carcinogenesis induced by BHP 20 . By contrast, no mutation of the Lpar2 , Lpar3 , Lpar4 and Lpar5 genes was detected in this model 21 .…”
Section: Genetic Alterationscontrasting
confidence: 61%
“…These findings demonstrated that Lpa1 mutations may be involved during rat lung and liver carcinogenesis. By contrast, no mutations of Lpa2, Lpa3, Lpa4, or Lpa5 genes were detected in lung adenocarcinomas induced by BHP [33]. In the present study, we also performed PCR‐SSCP analysis to evaluate whether Lpa5 gene mutations exist in rat tumor cell lines and HCCs, but detected no mutations.…”
Section: Discussionmentioning
confidence: 67%
“…Moreover, LPA1 gene mutations were also detected in not only lung adenocarcinomas but also preneoplastic lesions in rats [16]. In contrast, no mutations of the LPA2, LPA3, LPA4, and LPA5 genes were found in rat lung adenocarcinomas [22]. These findings suggest that the LPA1 gene mutations may play an important role in the development of rat tumor cells as well as aberrant LPA receptor gene expressions but not LPA2, LPA3, LPA4, and LPA5 mutations.…”
Section: Discussionmentioning
confidence: 82%